TANGGUNG GUGAT PERUSAHAAN PEMBANGUNAN PERUMAHAN YANG TIDAK MELAKSANAKAN PEMBANGUNAN RUMAHBAGI PEMBELI (Studi Kasus Perumahan The Sun Villages Damarsi Kabupaten Sidoarjo) - Tika Arista Roselyna; Sudarsono Sudarsono; Taufik Iman Santosa (Perpustakaan Universitas Surabaya, 2018)
A sale and purchase agreement is an agreement whereby one partycommitting itself to hand over property rights a material while the other party pay the price that had been promised. The preliminary sale and purchase agreement (PPJB) is an agreement to buy and sell a house that is still in the process of building between a prospective home buyer and a home provider that is known to the authorized official. The sale and purchase agreement is known as reciprocal agreement. It means,in an agreement, the parties have obligations to be fulfilled beside they will obtain rights. In some conditiont, fulfillment of obligations are not proceed as it should, which is a party does not fulfill its obligationts untill it causes condition that called breach of contract. The breach of contract cause consequences for the disadvantaged party to litigate the another party that cause breach of contract to give compensation.